Glass fiber and silica reinforced rigid polyurethane foams - M. W. Kim; S. H. Kwon; H. Park; B. K. Kim (eXPRESS Polymer Letters)
Ternary composites of rigid polyurethane foam (RPUF)/glass fiber/silica as well as RPUF/glass fiber have been fabricated from glass fiber, silica, polymeric 4,4′-di-phenylmethane diisocyanate (PMDI) and polyol using HFC 365mfc as blowing agent. Foam formation kinetics, morphology, thermal conductivity, glass transition temperature, decomposition temperatures as well as the mechanical strengths of the foam have been studied. With the addition an increasing amount of glass fiber cream time, rise time, gel time, tack free time, density, compression strength, thermal conductivity (k) monotonically increased while the glass transition temperature showed a maximum at 2%. At constant glass fiber content (2%), addition of silica further increased the process times, density and compression strength while the Tg and thermal decomposition temperature showed a maximum at 3% silica. The k value of RFUF/glass fiber composite decreased with the addition of silica up to 3%, where it was even lower than the virgin RPUF. However, beyond the content k value increased. Overall, the variation of k value with silica content showed identical tendency with cells size and closed cells content.